Meeting report from the first meetings of the Computational Modeling in Biology Network (COMBINE). Issue 2 (September 2011) - Novère, Nicolas; Hucka, Michael; Anwar, Nadia; Bader, Gary; Demir, Emek; Moodie, Stuart; Sorokin, Anatoly
Abstract TheComputational Modeling in Biology Network (COMBINE ), is an initiative to coordinate the development of the various community standards and formats in computational systems biology and related fields. This report summarizes the activities pursued at the first annual COMBINE meeting held in Edinburgh on October 6–9 2010 and the first HARMONY hackathon, held in New York on April 18–22 2011. The first of those meetings hosted 81 attendees. Discussions covered both official COMBINE standards-(BioPAX, SBGN and SBML), as well as emerging efforts and interoperability between different formats. The second meeting, oriented towards software developers, welcomed 59 participants and witnessed many technical discussions, development of improved standards support in community software systems and conversion between the standards. Both meetings were resounding successes and showed that the field is now mature enough to develop representation formats and related standards in a coordinated manner.